Evaluating and classifying railway stations in North Rhine-Westphalia. A methodological approach to operationalise Transit-Oriented Development - Eichhorn, Sebastian; Gerten, Christian; Diller, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
The concept of Transit-Oriented Development (TOD) aims to develop new residential and commercial areas in regionally integrated sites that provide future residents and employees with good local infrastructure, diversified public spaces and attractive mobility alternatives so that they do not have to use their own car. This paper presents a methodology for the operationalisation of Transit-Oriented Development and applies it to evaluate and cluster of 747 railway stations in North Rhine-Westphalia, Germany. Using the operationalised TOD dimensions, five interpretable clusters can be defined for North Rhine-Westphalia. The results show that the clusters with above-average TOD values in the dimensions destination accessibility, density and diversity can be found mainly in the Rhine-Ruhr region and in the solitary cities of North Rhine-Westphalia. In the peripheral areas, primarily clusters with lower TOD values occur. The findings indicate that there is a discrepancy between the availability of potentially developable building land and the degree of Transit-Oriented Development. In the surroundings of the railway stations of the high-capacity railway lines in regions with high demand for housing, there is barely any potential building land available. The majority of potential building land is located at railway stations with below-average TOD values and less pressure on the housing market. The clusters make it possible to formulate specific recommendations for action for urban planners and political decision makers in order to support a successful implementation of Transit-Oriented Development.
Keywords: Transit-oriented development; Operationalisation; Classification; Settlement development; Transport development; North Rhine-Westphalia